Electroactive Polymer Actuators and Devices (EAPAD) 2009 2009
DOI: 10.1117/12.817277
|View full text |Cite
|
Sign up to set email alerts
|

The influence of mechanical properties in the electrical breakdown in poly-styrene-ethylene-butadiene-styrene thermoplastic elastomer

Abstract: Dielectric elastomer actuators (DEA) are a class of eletro-active polymers with promising properties for a number of applications, however, such actuators are prone to failure. One of the leading failure mechanisms is the electrical breakdown. It is already well-known that the electro-mechanical actuation properties of DEA are strongly influenced by the mechanical properties of the elastomer and compliant electrodes. It was recently suggested that also the electrical breakdown in such soft materials is influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The measured voltage at failure is taken to be the electrical breakdown voltage. Experiments indicate that the breakdown voltage is a monotonically decreasing function of the prestretch È B ðÞ [23,27]. This trend may be interpreted as follows.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…The measured voltage at failure is taken to be the electrical breakdown voltage. Experiments indicate that the breakdown voltage is a monotonically decreasing function of the prestretch È B ðÞ [23,27]. This trend may be interpreted as follows.…”
mentioning
confidence: 87%
“…Also plotted is the condition for electrical breakdown È B ¼ E B H À2 . We have used representative values E B ¼ 2 Â 10 8 V=m, T ¼ 300 K, v ¼ 10 À27 m 3 , " ¼ 4 Â 10 À11 F=m, and H ¼ 1 mm [23,27]. To account for the uncertainty of the available experimental data, we have used a conservative value for FIG.…”
mentioning
confidence: 99%
“…This behavior is most likely related to the reduction of mechanical stiffness upon the alignment of PS nanodomains perpendicular to the electric field direction. In support to this hypothesis, few studies reported that the breakdown strength of SEBS was reduced with decreasing mechanical stiffness . In fact, the electrodes attached to the specimen's surface during the breakdown test exert a compressive force that might result in appreciable deformations at an applied voltage below the intrinsic breakdown voltage, especially in soft elastomeric materials, leading to reduced dielectric strength and failure.…”
Section: Introductionmentioning
confidence: 99%
“…The first material is the commonly used polyacrylic polymer VHB4910 [3], a pressure-sensitive glue (3M). For comparison, the thermoplastic SEBS500120 (SEBS12) [5] has been investigated as well. Unlike the ready to use VHBtape, SEBS films have to be prepared via drop casting.…”
Section: Introductionmentioning
confidence: 99%